Biocompatibility of Hydroxyapatite-Alumina and Hydroxyapatite-Zirconia Composites including Commercial Inert Glass (CIG) as a Ternary Component - (:unkn) unknown (GOLLER VERLAG GMBH, 2016)
Hydroxyapatite (HA), chemical formula Ca-10(PO4)(6)(OH)(2), is a very popular bioceramic for orthopedic and dental applications. Although HA has excellent biocompatibility, its inferior mechanical properties make it unsuitable for load-bearing implant applications. Therefore, HA should be strengthened by a secondary phase to produce a composite that possesses robust mechanical properties. The aim of this study was to compare the microstructural and mechanical properties and biocompatibility of HA-Al2O3 and HA-ZrO2 composites with the addition of 5 and 10 wt% commercial inert glass (CIG) independently and to determine from the studied composites the one with the most suitable composition for biomedical applications. The powders were pressed and then, the pellets were sintered between 1000-1300 degrees C for four hours. The thermodynamic analyses of the samples were performed by means of DTA followed by the thermodynamic analysis program FactSage. Microstructural characterizations were carried out using SEM + EDS and XRD, while hardness and compression tests were performed to measure the mechanical properties. The results showed that the compressive strength and the microhardness of HA-Al2O3 composites increased with rising CIG content and increasing sintering temperature. On the other hand, for HA-ZrO2 composites, increasing CIG content caused an elevation in hardness and a decrease in compressive strength values at 1300 degrees C. The biocompatibility tests (in vitro and in vivo) were performed on those composites that possessed the highest physical and mechanical properties. In conclusion, the optimum CIG content was determined to improve the mechanical properties and biocompatibility of the composites. The mechanical properties and biocompatibility of HA-Al2O3 composites have been found to be lower than those of HA-ZrO2 composites. In this study, the ideal composite was selected as HA-ZrO2-5 wt% (HZC5) sintered at 1200 degrees C.
Keywords: Hydroxyapatite; ceramics; composites; microstructure; mechanical properties; biocompatibility; MECHANICAL-PROPERTIES; BIOCERAMICS